2023
DOI: 10.15586/aei.v51i2.781
|View full text |Cite
|
Sign up to set email alerts
|

The role of Human Development Index in the epidemiology of asthma in adolescents in Kosovo

Abstract: Background: Very limited information is available on the prevalence and risk factors of asthma in adolescents in Kosovo, and no study has previously addressed the role of Human Development Index (HDI) on asthma in the region. The present study addresses these two issues.Methods: Following the Global Asthma Network (GAN) methodology, a cross-sectional survey, through standardised self-completed questionnaires, was conducted in the following six centres of Kosovo: Ferizaj, Gjakova, Gjilan, Peja, Prishtina and Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Demographic and environmental characteristics of the 6 Kosovar centres have been already described 15 . Table 1 shows the prevalence of current eczema symptoms, severe eczema symptoms and eczema ever overall, and with and without wheeze, together with the respective 95% confidence intervals.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Demographic and environmental characteristics of the 6 Kosovar centres have been already described 15 . Table 1 shows the prevalence of current eczema symptoms, severe eczema symptoms and eczema ever overall, and with and without wheeze, together with the respective 95% confidence intervals.…”
Section: Resultsmentioning
confidence: 99%
“…As for any GAN centre, all students (selected by grade or by age) of 13-14 years within all schools (Ferizaj, Gjakova, Gjilan, Peja, and Prizren) or within a random sample of them (Prishtina) were invited to participate to achieve the minimum required sample size of 1000. Additional details of the sample size and power are described elsewhere 12,14 Participation rates in Kosovo (80.0% or more) have been also described in detail previously 15 .…”
Section: Sample Size and Study Powermentioning
confidence: 99%
“…Asthma is a common chronic disease that affects people of all ages particularly for children. The Global Asthma Report showed that 14% of the world's children experienced asthma symptoms 1,2 . The prevalence of asthma is still increasing globally 2–4 .…”
Section: Introductionmentioning
confidence: 99%